ECOLOGICAL AWARENESS REPRESENTATION IN TOY STORY 4 MOVIE: A MULTIMODAL ANALYSIS - Safitri, Nabila Cahya; Kurniawan, Muhammad Hafiz (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2024)
The movie portrays aspects of human life, including ecological awareness, which extends beyond preserving natural elements like mountains and rivers to encompass human impact, waste, pollution, vehicles, and global warming. This research aims to examine how Toy Story 4 (2019) conveys ecological awareness through verbal and visual semiotics in selected scenes. The study focuses on a 3-minute and 20-second segment featuring Bonnie, the first character to display ecological awareness. Using a qualitative descriptive approach, 237 data points were analyzed based on theories by Kress Van Leeuwen, Baldry Thibault, and Halliday. These data were categorized into phases and sub-phases. While the film's utterances predominantly feature declarative moods (88%), along with imperative and interrogative moods (6% each), none directly address ecological themes. Instead, ecological awareness is visually represented in Toy Story 4 (2019) through visual grammar, particularly interactive meaning, to effectively illustrate and encourage environmental action for young audiences.